2019
DOI: 10.1029/2019gl084387
|View full text |Cite
|
Sign up to set email alerts
|

The Induced Magnetosphere of Mars: Asymmetrical Topology of the Magnetic Field Lines

Abstract: An asymmetrical pileup of the interplanetary magnetic field leads to an additional draping of the field lines in the opposite direction to the motional electric field. Such a draping and the associated magnetic field forces push the ionosphere plasma in the transverse direction opening a passage for an ion trail which contains dense and slowly moving plasma. We found that wrapping of the field lines around Mars starts in the hemisphere pointing in the direction of the motional electric field and propagates to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 35 publications
13
56
1
Order By: Relevance
“…Ion fluxes become much higher and the separation between the lobes and the plasma sheet in the central part of the tail almost disappears. Occurrence of the most intense ion fluxes with E > 30 eV is higher in the Z MSE > 0 hemisphere while the locus of maximum low‐energy ion fluxes is shifted to the Z MSE < 0 hemisphere, that is, in the agreement with the distribution of mean (median) ion fluxes in the tail (Dubinin, Modolo, et al., 2019).…”
Section: Observationssupporting
confidence: 52%
See 1 more Smart Citation
“…Ion fluxes become much higher and the separation between the lobes and the plasma sheet in the central part of the tail almost disappears. Occurrence of the most intense ion fluxes with E > 30 eV is higher in the Z MSE > 0 hemisphere while the locus of maximum low‐energy ion fluxes is shifted to the Z MSE < 0 hemisphere, that is, in the agreement with the distribution of mean (median) ion fluxes in the tail (Dubinin, Modolo, et al., 2019).…”
Section: Observationssupporting
confidence: 52%
“…Maximum fluxes of low energy ion are more often observed in the E − ‐hemisphere. Such a behavior is related to a shift toward the ‐Z MSE direction of the magnetic tail and the appearance of the ion trail which contains a dense and slowly moving plasma (Dubinin, Modolo, et al., 2019). Median values of the solar wind dynamic pressure and solar EUV flux during the measurements of maximum fluxes of ions with E > 30 eV and E < 30 eV correspond to disturbed solar wind conditions or high EUV values, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the induced magnetospheres of Mars and Venus have a various asymmetric behaviors between ±E hemispheres (e.g., Chai et al, 2016;Chai et al, 2019;Dong et al, 2015;Dubinin et al, 2019;Inui et al, 2019;Zhang et al, 2010). Harada et al (2017) clearly demonstrated by the MAVEN observations that magnetotail reconnection at Mars occurs preferentially in −E hemisphere rather than in +E hemisphere.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…Observations by Dubinin, Modolo, et al (2019) and Inui et al (2019) have shown that an asymmetry of escape fluxes between both hemispheres may also be related with the sign of the B y component of the IMF. This effect is related to features of the induced magnetosphere-the ionospheric plasma at the nightside is pushed in the direction opposite to the direction of the motional electric field in the solar wind.…”
Section: Discussionmentioning
confidence: 99%